Studi Komparasi Manajemen Kepala Sekolah antara Lembaga Pendidikan Umum dan Kejuruan Tingkat Menengah Atas - Saputri, Rafhita Ika; Asha, Lukman; Wanto, Deri (El-Idare, 2023)
This research aims to discover a comparison of school principal management in public schools and vocational schools in Banyuasin Regency. A case study was conducted in two schools, namely SMAN 2 Tungkal Jaya and SMKN 1 Tungkal Jaya. The approach used was a qualitative approach with interview data collection methods. Data was gathered through interviews with school administrators, teachers, and staff, as well as an analysis of documents related to school management. The research findings indicate that the management techniques of school principals differ between these two types of schools. Both institutions have different focuses in resource management and emphasis on educational goals and issues. Despite these differences, they both uphold the same policies in emphasizing educational excellence and student development. This study highlights how school principals manage schools that offer various forms of education in the same environment.